Mobius Band : establishing motion trajectory techniques to form woven apparel in a dynamic 3D space : this exegisis is presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Design at Massey University, Wellington, New Zealand. EMBARGOED until 15 June 2028. - Li, Zewei (Massey University, 2025)
The Mobius Band-inspired whole-garment weaving approach integrates its flexible motion trajectory, zero-waste pattern-making, and weaving techniques to create woven apparel without cut-and-sew practices, offering an alternative method to reduce textile waste in design and production. It integrates textile and fashion knowledge and practice to contribute to the evolution of the current linear system toward a multidimensional process that supports a sustainable future. This innovative approach challenges conventional thinking in both fashion pattern making and construction workflows, as well as conventional woven textile design and production norms. The Mobius Band provides a 3D dynamic space for design development, offering the potential for multiple forms and wear possibilities that fulfil and appeal to individual wearer preferences and size change. This research offers an alternative viewpoint to existing mindsets in apparel design and production when pursuing sustainable technological innovations. It encourages designers to think and approach woven apparel beyond the 2D flat surface, challenging conventional processes and systems that continue to devalue fabric and apparel. Conventional linear woven textile and fashion production systems exacerbate the division of knowledge and labor. In this research, a simultaneous design approach was employed to seamlessly merge textile and fashion practices. The intention being to form woven whole-garments in a hybrid manner within the context of slow production to transition towards a less wasteful industry. An action research methodology was utilized to facilitate an iterative process of exploratory techniques and prototyping to ensure the knowledge is developed with the interdisciplinary consideration of both textile and fashion. The work began by exploring how the Mobius Band structure in fashion could be used to challenge conventional pattern-making and zero-waste pattern-making methods that start with 2D flat surfaces with a 3D dynamic space for garment development. The flexible motion trajectory of the Mobius Band, a crucial result of the first stage of research, serves as a pivotal shift in thinking- reframing the use of the Mobius Band from a structural concept to one of perpetual motion, from conventional garment patterning to simultaneously weaving and patterning. The 3D whole-garment knitting technique, with its dynamic yarn movement, inspired early research into shaping a 3D whole-garment through weaving with a continuously moving weft yarn. The outcome demonstrates the potential of utilizing the motion trajectory of the Mobius Band to create woven garments through hand-weaving with computer- controlled looms, incorporating size-inclusive and adaptive design features to support the needs of diverse body shapes. This research proposes an alternative approach to woven apparel design and production that responds to current issues of textile waste, with the intention of highlighting the value of craft, fabric, and garment integrity.
Embargoed until 15 June 2028
Keywords: 330315 Textile and fashion design; 330314 Sustainable design